Totalitas Cinta dalam Syair Rabi'ah Al-Adawiyah: Tinjauan Semiotika Pierce - Fitriani Fitriani (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2021)
This study aims to review the totality of love in Rabia'ah Al Adawiyah's poetry based on the semiotic perspective of Charles Sanders Peirce, namely icon, index, and symbol. The research process was carried out using a descriptive-qualitative method. The results found that there were two forms of icons, eight forms of indexes, and three forms of symbols which were analyzed from the seven poems mentioned in the study. The form of totality of love by Rabi'ah's love is described by of index and symbol. The author concludes that from the eight indexes, the totality of love described by sacrifice, willingness, a sense of closeness, fear of making mistakes, unwillingness to rewards, and unwillingness to another. The totality of love in symbols form is described by word